THE SIGNIFICANCE OF RELIGIOUS KNOWLEDGE AND PRACTICE AS PART OF CONTRIBUTIONS OF MUSLIM HAPPINESS - Ateerah Abdul Razak; Lukman Z.M; Amanina Abdul Razak @ Mohamed (Journal of Islamic, Social, Economics and Development, 2023)
Religious knowledge and practice are the main elements for individuals to attain a balanced wellbeing in life. For humans who have faith inside, they will make sure that they fulfill the criteria to achieve a healthy life spiritually, physically and emotionally. However, there is a scarcity of research analyse the instruments using the components as a measurement for Muslim happiness. Thus, this study tries to measure several items related to religious knowledge and practice as contributors for Muslim happiness . This study adopts an overview of Muslim scholar Al-Ghazali's view of happiness, and it employs a review of previous literature and compiles it into several domains which contain items related to the evaluated subject. It also identifies that religious knowledge and practice play an important role for Muslim happiness. The current study has gone through several validity processes such as content validity which is endorsed by the experts in several related fields, exploratory factor analysis (EFA) and finally the process of Confirmatory Factor Analysis (CFA) using Smart-PLS. The sampling method uses purposive technique that consist of Malaysian Muslim across several states in Malaysia and they were among 18-75 years old. It can be observed that there is a significant relation between practices and happiness (t=6.805, p<0.000), and religious knowledge and happiness (t=3.947, p<0.000). This study suggests that the components of religious knowledge and practice should become practical among Muslim to attain a balanced well-being and happiness in life and the hereafter.